2014
DOI: 10.1007/s12010-014-1213-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of Electroporation Pre-treatment on the Biogas Yield from Ley Crop Silage

Abstract: Exploiting the full biogas potential of some types of biomass is challenging. The complex structures of lignocellulosic biomass are difficult to break down and thus require longer retention times for the nutrients to become biologically available. It is possible to increase the digestibility of the substrate by pre-treating the material before digestion. This paper explores a pre-treatment of ley crop silage that uses electrical fields, known as electroporation (EP). Different settings of the EP equipment were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…It was concluded that permeabilization of switch grass and wood chip species using the PEF can be utilized to improve the cellulose hydrolysis to sugar. Electroporation of lignocellulosic biomass (ley crop silage) under the PEF treatment (at E = 48-96 kV/cm) has been investigated (Lindmark et al 2014). Ley crop (a mixture that consists mainly of grass and clover) is commonly used in a crop rotation to fertilize a soil with nitrogen.…”
Section: Wood and Crop Biomasses: Sawdust Chips Barks Silage And mentioning
confidence: 99%
“…It was concluded that permeabilization of switch grass and wood chip species using the PEF can be utilized to improve the cellulose hydrolysis to sugar. Electroporation of lignocellulosic biomass (ley crop silage) under the PEF treatment (at E = 48-96 kV/cm) has been investigated (Lindmark et al 2014). Ley crop (a mixture that consists mainly of grass and clover) is commonly used in a crop rotation to fertilize a soil with nitrogen.…”
Section: Wood and Crop Biomasses: Sawdust Chips Barks Silage And mentioning
confidence: 99%
“…Moreover, strong shockwaves generated by methods such as sparking are able to crack conglomerates (plant debris, lignocellulose, manure, soil), making carbon sources better available 8 . Although postulated in earlier days, there is no evidence that shockwaves are able to crack lignin, but electrical treatment can enhance digestion of ligno-cellulose rich material 48 .…”
Section: Shockwavementioning
confidence: 99%
“…The results from the previous studies by the authors on pre-treatment and membrane filtration of the process water [5,6,16] presented in Table 1 and 2 were used to estimate what it would mean for the full-scale biogas plant if these measures are taken. The results of the studies were also converted to the same form to be able to compare them.…”
Section: Potential For Biogas Plant Performance Improvements By Pre-tmentioning
confidence: 99%
“…Therefore pre-treatment of the ley crop silage to increase the digestion rate is of interest to improve the performance of the plant. Mechanical pre-treatment and pre-treatment by electroporation of ley crop silage has previously been studied by the authors [5,6]. In the mechanical pre-treatment tests two commercial available grinding machines for recovering of fibres from recycled paper were used, GLD 360 HW and KD 450 from Cellwood Machinery AB.…”
Section: Introductionmentioning
confidence: 99%